Un problema urgente: la dispersione scolastica. Note sul caso-Finlandia - Giosi, Marco (Studi sulla Formazione/Open Journal of Education, 2011)
This research aims to investigate and analyze the phenomenon of school drop-out in Italy through a comparison with those models, the Finnish first and foremost, in which this phenomenon appears to be significantly reduced. It will, therefore, to examine what are the unique aspects of their education system in Finland, taking into account the specificities of the social, economic and cultural context, with particular attention to the issue of dispersion, trying to identify possible transferable solu- tions to our school system, with particular reference to the upper-secondary school.